A new model of transformer operation state evaluation based on analytic hierarchy process and association rule mining. (19th June 2021) - Zhou, Zhenyu; Xu, Huigang; Ye, Haifeng
In order to establish a transformer state evaluation model for power grid operation and maintenance management, based on the aging mechanism of transformer, a state risk evaluation method based on the Analytic Hierarchy Process (AHP) and the association rule mining is proposed. Based on the big data analysis of the actual state quantity of the transformer, the subjective weight coefficient of different state quantity is determined by the analytic hierarchy process. The objective weight coefficient of the comprehensive state quantity is determined by the association rules mining. And the fusion of the subjective weight coefficient and the objective weight coefficient is completed according to the weight coefficient fusion technology of the mean square deviation method. The practical results show that the model in this paper can evaluate the operation state of transformer comprehensively and accurately.